The Effectiveness of Cognitive Behavioral Program in Reducing Psychological Stress among Female Teachers of Students with Special Needs in Jordan - Bani- Mustafa, Manar Saeed; Al-Shiyab, Shereen Mahmood (Dirasat: Educational Sciences, 2020)
The study aims at examining the effectiveness of cognitive behavioral programs in reducing psychological stress among female teachers of students with special needs in Jordan. To achieve the purpose of the study, the researcher designed a scale measuring psychological stress among the teachers. The sample consisted of (31) female teachers working at Al-Biqa’i Institution for Comprehensive Care and Rehabilitation in Irbid. The teachers were divided into two groups. The first group is an experimental group consisting of 16 teachers who all received (12) counseling sessions, (2) sessions per week. Each session extended for 60 minutes for each session. The control group consisted of 15 female teachers who did not receive any training program. The results of the study revealed statistically significant differences between the means scores of the experimental and control groups on the scale of psychological stress and its dimensions in favor of the experimental group who were trained using a training program. In addition, the effect size for the counselling program was (94.31), confirming the high effect of the training program in reducing psychological stress among Jordanian female teachers of students with special needs.